MEMBERDAYAKAN TENAGA KEPENDIDIKAN ANAK USIA DINI MELALUI PROGRAM SIMBIOSIS - Kurniawan Catur Hidayat (Direktorat Pembinaan Guru dan Tenaga Kependidikan Pendidikan Anak Usia Dini Kementerian Pendidikan dan Kebudayaan bekerjasama dengan Fakultas Ilmu Pendidikan Universitas Negeri Jakarta, 2010)
Symbiotic programs provide alternative solutions to improve the quality of educators and teachers of non-formal education through the cooperation of mutual assistance between them. The programs provide a positive reciprocity between students majoring in Early Childhood Education and the teachers of Early Childhood Education in schools. The programs are conducted in the form of exchanging the theory and application of various knowledge of child education, media development, and